Navigating the fourth industrial revolution: Taxing automation for fiscal sustainability. Issue 4 (November 2019) - McCredie, Bronwyn; Sadiq, Kerrie; Chapple, Larelle
The fourth industrial revolution has arrived; however, this industrial revolution is unlike those witnessed in the past. Equal opportunity and growth have been replaced by the 21st century trend of rising inequality, in which advancement through digitisation and automation brings fortune to the few and hardship to the many, as income and property stratification grows. As a result, current tax systems are under pressure with displaced workers requiring support, and the fiscal purse, which has historically been funded by income taxes, being eroded due to a decreasing number of workers to tax. Conceivably, it is up to governments to address this 'double negative effect', but it is unclear how this could be achieved and what theoretical basis should be leveraged to do so. This article provides a discussion of three important normative philosophies of distributive justice, utilitarianism, libertarianism and John Rawls' theory of justice, to determine a theoretical basis on which the redistribution of income via a tax on automation is justified. The pertinent theory is then operationalised with the proposal of three alternate models of taxation: a Pigouvian tax, a tax on economic rents and an appreciation tax. Each of these models is evaluated alongside a discussion on the shift in global tax policy from taxing income to taxing capital. This article argues that this shift is necessary to reduce income inequality and to ensure even the lowest common denominator is provided for, for we are the 99%. JEL Classification:H23, H25, K34, O23